Secure semantic service-oriented systems - Thuraisingham, Bhavani M. (Auerbach Publications, 2011)
Presents an exploration of security issues for the SOA and web services. This book demonstrates the applications of these technologies in multiple domains. It features discussions of concepts in trustworthy information systems and security for SOA. It covers secure web services and applications